Effect of boron segregation on bainite nucleation during isothermal transformation. (15th January 2022) - Douguet, P.; Da Rosa, G.; Maugis, P.; Drillet, J.; Hoummada, K.
Abstract: The effects of boron segregation and austenite grain size on the bainitic isothermal transformation of a high-strength steel were studied independently. Dilatometry, microstructural observations and previous atom probe tomography analyses showed that bainitic transformation rate decreases with increasing boron excess at austenite grain boundaries. We also found that boron segregation causes an unexpected grain size effect: large austenite grains transform faster than small ones. A kinetic model assuming slow nucleation at austenite triple junctions and rapid growth of bainitic nuclei successfully described our experimental data. These results confirm that bainite nucleation is inhibited by segregated boron at grain boundaries. On this basis, austenitic grain size could be optimized to make the most of boron addition in advanced high-strength steels. Graphical abstract: Image, graphical abstract